Blockchain and cloud platforms in banking services: A paradox perspective - Piotr Łasak; Sławomir Wyciślak (Journal of Entrepreneurship, Management and Innovation)
PURPOSE: The banking sector is under intense pressure from digitalization. One of the accompanying processes is the development of digital platforms and platform ecosystems in banking services. The paper aims to present the dynamic pattern of behavior among partners stemming from the tensions between governance costs and co-created value within platforms in banking services. METHODOLOGY: The study employs an approach based on a systematic literature review of 54 publications selected from Scopus and WoS databases. We applied an approach that consists of two steps. The first step of the research was a literature review and critical analysis of the sources related to our research questions. In the second step, we propose a causal loop diagram research procedure, which is a research system dynamic tool used in modeling system dynamics. FINDINGS: There are different types of platforms, and among the most important are blockchain-based and cloud-based platforms. In both types, the relations between owners, complementors, and customers are important. The tension between governance costs and co-created value informs behavior patterns among platform partners. The degree of interconnectedness between platform participants and the level of centralization of banking services depends on the platform type. The study highlights that blockchain-based and cloud-based platforms play a significant role in the transformation of the current banking services. The choice of platform type has important implications for the platformization of banking services. IMPLICATIONS: The pattern of behavior among platform partners identifies the self-reinforcing dynamics that suggest how managers can navigate the tension over time amidst the asymmetry of benefits and risks. The research findings can be informative for financial regulators and they help work out a policy that reduces the asymmetry of benefits and contributes to the more sustainable development of digital platforms. ORIGINALITY AND VALUE: This paper addresses the paradox perspective on the banking sector changes during the intensive processes of digitalization and the creation of new ‘platform ecosystems.’ This topic has not been studied in this context so far.